The role of “network of cities” in construction of global urban culture - Tüzin Baycan-Levent; Seda Kundak; Aliye Ahu Gülümser (European Regional Science Association (ERSA), 2004)
The globalization process has led to an increased interaction between cities and to a new urban system/network in which they need to be competitive and complementary at the same time. “Network of cities”, such as World Cities, Eurocities or Sister Cities are among the well known examples of interaction and cooperation of the cities at the regional and global level. The cities of different regions and countries tend to share their experiences and their cultures within these networks in order to develop some common spatial or social strategies and further cooperation. “Best practices” or “benchmarking are the most important issues of the interaction between cities. While benchmarking facilitates the cultural dialogue between different cities, the common values developed in this process make a great contribution to the construction of global urban culture. The main aim of this paper is to investigate the role of urban networks in the interaction and integration of cities by means of “Sister City” movement that can be defined as a partnership of two cities from different countries which is based on cultural and social understanding to achieve cultural dialogue. This paper focuses on the “Sister Cities of Instanbul” to highlight the development process of the movement in the historical and geographical context and to evaluate the development phases of the relationship with sister cities. The results of our study show that Istanbul's relationships with its sister cities are at the “associative” and “reciprocative” phases that can be defied as the earlier phases of the relationships.
Keywords: 330